Propriedades fotoluminescentes do CuMoO4 - Santos, Valdemir dos (Universidade Federal de São Carlos, 2011)
In this study, CuMoO4 were synthesized, characterized and crystallized into powders in two structures: monoclinic and triclinic. CuMoO4 powder were synthesized by precipitation, and the reaction s pH were controlled due to the importance of pH in the process of development CuMoO4. The powder was processed at 140°C at different times in hydrothermal assisted by microwave irradiation, it is possible to prepare materials that have different structure organization degrees. The structural and morphologic properties of these materials were analyzed through X ray diffraction, transmission electronic microscopy, photoluminescence spectroscopy and zeta potential, among anothers. Using those techniques, it was possible to observe the pH s influence in the solution and its reflex in the structural development, where there are two differents structures competing in solution (Triclinic and Monoclinic). The structural organization leads the mechanisms of FL by its cluster position (order disorder). The evolution of the structural disorder at short range was controlled by using the HM, and its reflexes could be observed in the FL. The photoluminescent emissions in blue and red were attributed to clusters [Mo4] and [MO6] and its space position, which were modified by HM. The difference between the emission maxima and minimal was assigned to distinct photoemission mechanisms that are related to the electronic structure of these materials
Photoluminescence properties of CuMoO4
Keywords: Físico-química; Potencial zeta; Hidrotérmico Microondas; Pentaquocobre II; Ordem-desordem estrutural; CIENCIAS EXATAS E DA TERRA::QUIMICA